Proceedings of the 3rd International Conference on Intelligent Technologies and Engineering Systems (ICITES2014) - Juang, Jengnan (Lecture Notes in Electrical Engineering,, 2016)
This book includes the original, peer reviewed research from the 3rd International Conference on Intelligent Technologies and Engineering Systems (ICITES2014), held in December, 2014 at Cheng Shiu University in Kaohsiung, Taiwan. Topics covered include: Automation and robotics, fiber optics and laser technologies, network and communication systems, micro and nano technologies, and solar and power systems. This book also Explores emerging technologies and their application in a broad range of engineering disciplines Examines fiber optics and laser technologies Covers biomedical, electrical, industrial, and mechanical systems Discusses multimedia systems and applications, computer vision and image & video signal processing.